Occurrence of Hirudinea species in a post urban reach of a Patagonian mountain stream - Miserendino, Maria Laura (2014)
Temporal (May 2005 to February 2006) and habitat distribution (pools and riffles) of Hirudinea species was analyzed at a post urban reach from Esquel stream (Chubut province, Patagonia, Argentina). Site was located 5.7 km downstream a Waste Treatment Plant. Mean values of nutrients: ammonia, nitrates and soluble reactive phosphate, as well water conductivity, turbidity and total suspended solids indicated physical and organic pollution. Leeches assemblage was composed by the glossiphonids: Helobdella scutifera Blanchard, 1900, H. michaelseni (Blanchard, 1900),H. simplex (Moore, 1911), Helobdella sp., H. hyalina Ringuelet, 1942, H. obscura Ringuelet, 1942 and the semiscolecid Patagoniobdella variabilis(Blanchard, 1900). From these H. hyalina and H. obscura are new records for Chubut province. Helobdella hyalina (810 ind.m ^-2) and H. simplex(465 ind. m ^-2) clearly dominated the assemblage at the reach. Only H. simplex displayed a spatial preference being significantly more abundant inpools than in riffle habitats.